The Good Governance Level’s Profile of Sport Organization in Central Java (Department of Physical Education, Sport, Health and Recreation, 2018)
The aim of this research is to get the level of good governance of Sports Organization in Central Java. This quantitative descriptive research conducted at sports organization in 29 cities throughout Central Java. The questionnaire used was the Action for Good Governance in the International Sports Organization (AGGIS) Sports Governance Observer developed by the Danish Institute of Sports Studies, Denmark and data analysis used the Sports Governance Observer (SGO) Index to generate the average percentage score of four dimensions. From the analysis result, Kota Salatiga and Kota Pekalongan have the highest level of good governance with 60%. However, Kabupaten Tegal becomes the lowest level of good governance, 21.88%, and overall, the average level of good governance of sports organizations in Central Java is only 38.62%. The low average score has affected by the transparency rate, only 37%, because the organization does not have a website or social media so the community to monitor the use of budget and activities. Later this initial data could be a basis for determining the policy in improving the good governance and similar research can be done every one period